Challenges in pharmacologic management of the hospitalized patient with psychiatric comorbidity. Issue 9 (31st July 2013) - Ward, Martha; Schwartz, Ann
<x xml:space="preserve">Abstract</x> BACKGROUND Psychiatric comorbidity is common in the inpatient medical population. Hospitalists are frequently faced with decisions regarding the psychopharmacologic management of medically ill patients, yet receive limited psychiatric training. This review aims to assist the hospitalist in making an informed decision about the continuation of home psychotropic medications in the medically ill patient. METHODS A PubMed literature review was performed to obtain information on the effects of psychotropic medication discontinuation. In addition, the literature was reviewed regarding the potential challenges of psychotropic medication continuation. RESULTS A growing number of studies demonstrate high rates of relapse when medications are discontinued in patients suffering from mood disorders, schizophrenia, and anxiety disorders. Abrupt cessation of psychotropics is especially dangerous, leading to a greater chance of destabilization. Discontinuation syndromes, with prominent physical symptoms, may also result from sudden psychotropic cessation. Conversely, continuing home psychotropic medication may cause adverse effects due to drug‐drug interactions or changing pharmacokinetics. CONCLUSIONS This review examines the risks of psychotropic discontinuation as well as the challenges of psychotropic continuation in the medically ill patient. When making complex psychopharmacologic decisions, hospitalists should employ all available resources, including pharmacists and consult‐liaison psychiatrists. Ultimately, physicians and patients must make collaborative decisions, weighing the risks and benefits of psychiatric medications. Journal of Hospital Medicine 2013;8:523–529. © 2013 Society of Hospital Medicine